2004
DOI: 10.1007/s00441-004-0982-7
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of the antennal glands in the crayfish Astacus leptodactylus (Crustacea, Decapoda): anatomical and cell differentiation

Abstract: The ontogeny of the antennal glands was studied during the embryonic and post-embryonic development of Astacus leptodactylus. The future glands arising from undifferentiated columnar cells were detectable at the metanauplius stage EI 150 microm (EI: eye index; approximately 440 microm at hatching). The tubule and labyrinth differentiated in embryos at EI 190 microm, and the bladder and coelomosac at EI 250 microm. At EI 350 microm, the tubule lengthened and divided into proximal and distal sub-regions. In late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 41 publications
(60 reference statements)
5
31
0
1
Order By: Relevance
“…A firm explanation of this phenomenon is still lacking. This feature might represent the secretory function of the apocrine products instead of the reabsorbtion function of these labyrinth cells, as has been reported in crayfish (Sesma et al 1983;Fuller et al 1989;Khodabandeh et al 2005a). Conversely, it can also be interpreted as the debilitating effect of low salinity on the excretory cells, which could have, as a consequence, shrimp mortality upon prolonged exposure to low salinity, which has generally been observed by shrimp farmers.…”
Section: Discussionmentioning
confidence: 81%
“…A firm explanation of this phenomenon is still lacking. This feature might represent the secretory function of the apocrine products instead of the reabsorbtion function of these labyrinth cells, as has been reported in crayfish (Sesma et al 1983;Fuller et al 1989;Khodabandeh et al 2005a). Conversely, it can also be interpreted as the debilitating effect of low salinity on the excretory cells, which could have, as a consequence, shrimp mortality upon prolonged exposure to low salinity, which has generally been observed by shrimp farmers.…”
Section: Discussionmentioning
confidence: 81%
“…diffusion access distances), or that the mechanism(s) of Na + uptake is (are) fundamentally different in neonates and adults. Notably, ontogenetic changes seen in hyper-regulating crustaceans are generally associated with anatomical and/or structural changes in the ion-transporting cells and organs (Charmantier and CharmantierDaures, 2001;Charmantier et al, 2002;Cieluch et al, 2004;Khodabandeh et al, 2005a;Khodabandeh et al, 2005b).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, physiological studies have clearly demonstrated that significant changes in the ability to cope with hypo-osmotic environments occur during the ontogenesis of the osmoregulatory organs in various crustacean groups, including cladocerans (daphnids), isopods, amphipods and decapods (crabs, lobsters, shrimps and crayfish) (Charmantier, 1998;Charmantier and Charmantier-Daures, 2001;Charmantier et al, 2002;Cieluch et al, 2004;Khodabandeh et al, 2005a;Khodabandeh et al, 2005b). The ontogenesis of the osmoregulation can occur at either the embryonic or the postembryonic phase (Charmantier and Charmantier-Daures, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true in the Astacidea, in which the structure of the antennal glands has been described in several species of crayfish (review in Khodabandeh et al 2005a). These studies have shown that each antennal gland is composed of a single nephron-like unit including the coelomosac, the labyrinth, the nephridial tubule (nephridial canal), and the urinary bladder.…”
mentioning
confidence: 99%